The global research of microbiota in colorectal cancer screening: a bibliometric and visualization analysis - Zhen, Junhai; Liu, Chuan; Liao, Fei; Zhang, Jixiang; Xie, Huabing; Tan, Cheng; Dong, Weiguo (Frontiers in Oncology, 2023)
Aims We conducted bibliometric and visualization analyses to evaluate the current research status, hotspots, and trends related to the human microbiota markers in colorectal cancer screening. Methods The related studies were acquired from the Web of Science Core Collection (WoSCC) database on 5 January 2023. Analyses of the co-occurrence and cooperation relationships between the cited authors, institutions, countries/regions, cited journals, cited articles, and keywords in the studies were carried out using CiteSpace 5.8.R3 software and the Online Analysis platform of Literature Metrology. Additionally, relevant knowledge graphs were drawn to perform visualization analyses; a keywords cluster analysis and a burst analysis were also conducted. Results After analyzing 700 relevant articles, this bibliometric analysis found that the annual publications showed an increasing trend from 1992 to 2022. Yu Jun from the Chinese University of Hong Kong had the highest cumulative number of publications, whereas Shanghai Jiao Tong University was the most productive institution. China and the USA have contributed the largest number of studies. The keywords frequency analysis demonstrated that “colorectal cancer,” “gut microbiota,” “Fusobacterium nucleatum,” “risk,” and “microbiota” were the most frequent keywords, and the keywords cluster analysis found that the current hotspots were as follows: (a) the precancerous lesions of colorectal cancer (CRC) that need to be screened, such as inflammatory bowel disease (IBD) and advanced adenoma, (b) the gut-derived microbiome for CRC screening, and (c) the early detection of CRC. The burst analysis further showed that the combination of microbiomics with metabolomics might be the future research trend in the field of CRC screening. Conclusion The findings of the current bibliometric analysis firstly provide an insight into the current research status, hotspots, and future trends in the field of CRC screening based on the microbiome; the research in this field is becoming more in-depth and diversified. Some human microbiota markers, especially “Fusobacterium nucleatum,” are promising biomarkers in CRC screening, and a future hotspot might be the combined analysis of microbiomics and metabolomics for CRC risk screening.